المهالبة ودورهم في التاريخ العربي الإسلامي حتى قيام الدولة العباسية - يونس, محسن (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
عُرف المهلب وآله في التاريخ العربي الإسلامي بشهرتهم السياسية والعسكرية, وارتبط صيتهم في داخل شبه الجزيرة العربية وخارجها بالمنجزات السياسية والعسكرية المهمة التي أنجزوها في الدولة الإسلامية منذ قيامها على يد الرسول صلى الله عليه وسلم مروراً بالدولة الأموية حتى قيام الخلافة العباسية, وقد تجلّى ذلك باشتراكهم بأعمال الفتوح على الجبهة الفارسية بخاصة, واعتماد الخلفاء الأمويين عليهم اعتماداً كبيراً في حرب الخوارج وتدميرهم, ومن هنا رأينا أنه من الأهمية بمكان أن نبرز دور هذه الأسرة العربية –ورجالها العظماء في تاريخ العرب والإسلام . Some Arab men of the Islamic Period were especially important in the role they played at both the political and military levels. One of the most prominent of such personalities of the Omayyad State was Al-Muhalab Bin Sagheera, who provided great service to a number of Omayyad Caliphs, particularly during Caliph Abd Al-Malek Bin Marwan's rule. Bin Marwan entrusted Bin Sagheera in maintaining peace in the eastern part of the Islamic State. Bin Sagheera accomplished this mission perfectly well, silencing Al Khawarejs' dissenting voice and eliminated them. He also took part in the invasion of the countries situated beyond the River, thus deserving the Caliph's reward: appointment of Khurasan.